Disorderly Theory: Review of Sundhya Walther, Multispecies Modernity: Disorderly Life in Postcolonial Literature - Sandhar, Jason (Humanimalia, 2023)
Review of:Sundhya Walther. Multispecies Modernity: Disorderly Life in Postcolonial Literature. Environmental Humanities series. Waterloo, Ontario: Wilfrid Laurier University Press, 2021. 278 pp. CA$85.00 (hb).